Функції статутного капіталу за законодавством України - Хорт, Ю.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Статья посвящена исследованию функций уставного капитала по законодательству Украины. Автор формулирует собственное определение правообеспечительных функций и проводит их классификацию на основные и производные (дополнительные). Даются предложения по усовершенствованию действующего законодательства. The article is devoted to research of the functions of the share capital under Ukrainian legislation. The author formulates own definition of share capital legal functions and gives their classification into basic and complementary. The prepositions as to the current legislation improvement are given by the author.